IMPLICATIONS OF NICKEL ORE EXPORT RESTRICTIONS ON MINERAL SECTOR TRADE IN INDONESIA IN 2020-2023 - Chamelia, Nala; Cahyani, Afni Regita (Mediasi Journal of International Relations, 2024)
Limiting nickel ore exports is a government effort to protect and prevent depletion of mineral resources, especially nickel. One form of government policy is to limit the export of raw nickel ore by processing raw nickel ore so that it has added value to the downstream nickel industry in the global market. With so many other countries' interest in Indonesian nickel, the Indonesian government protects Indonesian nickel. This study aims to analyze the implications of Indonesia's nickel export protectionism policy on mineral sector trade. This research uses deductive qualitative research methods with literature review data collection techniques from secondary data sources. The theory used in this research is the theory of protectionism. The results of this study indicate that protectionist measures taken by the Indonesian government have a significant impact on the mineral sector and the national economy, because Indonesia is the largest nickel producer in the world. Protectionism efforts by the Indonesian government have an impact on sustainable development and creating economic independence from the nickel industry.